Optimalisasi E-Learning dengan Analisis Kelayakan Learning Management System TutorLMS untuk Startup Education Technology - Irji Rizqi Sabila; Ardiansah, Irfan; Yohari, Amili (Unversitas Muhammadiyah Riau, 2023)
The world of education should rightly be the spearhead of a country's progress, with its diversity of learning as well as the means of supporting education itself. With the rapid development of science and technology which requires education to collaborate with the latest technology, there are more and more digital-based and online educational methods and media, one of which is the Learning Management System. Due to the demand to improve the quality of learning for students and teachers, online tutoring companies such as Nurstech.id must have a learning management system that can accommodate all online learning activities by relying on a Learning Management System. TutorLMS was chosen as an online educational medium that can accommodate all the students' online tutoring needs. The feasibility analysis carried out is an optimization of the TutorLMS application, available features, and an increase in company resources. The resulting TutorLMS application is to facilitate teaching and learning activities carried out by students and teachers. The features owned by TutorLMS help learning activities as support or learning media to make it easier for teachers to provide information and learning materials to students quickly and easily. Increasing company resources is directly proportional to improving the quality of tutoring as well as added value that can increase competitiveness with competitors. These results indicate that the application of learning media with the TutorLMS Learning Management System can be said to be good with added value and benefits obtained after the research is carried out. With these results, Nurstech.id needs to do several things to improve the quality of its tutoring performance by implementing the TutorLMS Learning Management System and maximizing the quality of its tutoring performance by using the tools provided by TutorLMS.